Resident cats in small animal veterinary hospitals carry multi-drug resistant enterococci and are likely involved in cross-contamination of the hospital environment - Ghosh, Anuradha; KuKanich, Kate; Brown, Caitlin E.; Zurek, Ludek (Frontiers in Microbiology, 2012)
In the U.S., small animal veterinary hospitals (SAVHs) commonly keep resident cats living permanently as pets within their facilities. Previously, multi-drug resistant (MDR) enterococci were found as a contaminant of multiple surfaces within such veterinary hospitals, and nosocomial infections are a concern. The objectives of this study were to determine whether resident cats carry MDR enterococci and if they potentially play a role in the contamination of the hospital environment. Enterococcal strains (n=180) were isolated from the feces of six healthy resident cats from different SAVHs. The concentration of enterococci ranged from 1.1 x 105 to 6.0 x 108 CFU g-1 of feces, and the population comprised E. hirae (38.3±18.6%), E. faecium (35.0±14.3%), E. faecalis (23.9±11.0%), and E. avium (2.8±2.2%). Testing of phenotypic resistance to 14 antimicrobial agents revealed multi-drug resistance (≥3 antimicrobials) in 48.9% of all enterococcal isolates with most frequent resistance to tetracycline (72.8%), erythromycin (47.8%), and rifampicin (35.6%). Vancomycin resistant E. faecalis (3.9%) with vanB not horizontally transferable in in vitro conjugation assays were detected from one cat. Genotyping (pulsed-field gel electrophoresis) demonstrated a host-specific clonal population of MDR E. faecalis and E. faecium. Importantly, several feline isolates were genotypically identical or closely related to isolates from surfaces of cage door, thermometer, and stethoscope of the corresponding SAVHs. These data demonstrate that healthy resident cats at SAVHs carry MDR enterococci and likely contribute to contamination of the SAVH environment. Proper disposal and handling of fecal material and restricted movement of resident cats within the ward is recommended.